Imede mõistmisest eestikeelsete õigeusklike seas - Eek, Liina (Usuteaduslik Ajakiri, 2016)
Miracles and Their Interpretation among Estonian-Speaking Orthodox People This article describes experiences and beliefs of Estonian-speaking Orthodox people with miracles. The article isbased on empirical data, collected between 2012-2014, gained from 57 semi-structured interviews with Estonianspeaking clergy and lay members of both Estonian official Orthodox churches - the Estonian Apostolic Orthodox Church and the Estonian Orthodox Church of Moscow Patriarchate. The age of informants was between 22 and 89 years. The data was analysed using qualitative content analysis. Miracle in this article is understood as a suprarational or extraordinary event that is experienced personally. Such events are connected with saints, their relics, angels, icons, Mother of God or God Himself, from whom an informant receives revelations or messages, and who answers to the prayers of the informant. Other forms of miracles that are known in Orthodox tradition have not been discussed in this article. The results show that the majority of Estonian-speaking Orthodox people do believe in some kind of miracles. Even though these results cannot be generalized to all Orthodox population in Estonia, I could say that there are only few Orthodox being sceptic, and most of the informants believe in angels, saints or (miraculous) icons. E.g., only one of my informants claimed that miracles were not possible, all the other sceptical informants were hesitant in the worst case, but they did not exclude the possibility that miracles could occur in certain cases. In general, the informants were able to connect their beliefs and experiences with Orthodox theology, butin certain cases I could also find some New-Age elements. Those elements were more abundant among informants whose knowledge about Orthodox theology and dogmas is exiguous. Even in those cases the Estonian Orthodox people tend to interpret the miracles in the Christian context and miraculous events are taken as facts that affirm their belief in God.